O significado da comunicação na assistência de enfermagem à mulher mastectomizada : o olhar de quem cuida - Araújo, Iliana Maria de Almeida (2006)
The breast cancer is reason of great fear in the society in general and mainly in the women, in result of the raised index of morbi-mortality and mutilation, with consequent compromised of auto-they esteem and of the personal development of who it is for carrier it. However, intervenes excessively with social, personal, professional and affective the relations, Therefore to know as the nurse communicates itself with this clientele was the fidget for the accomplishment of this study, whose objective was to understand the communication process patient nurse/, emphasizing the meaning, values and possibilities of change in the assistance of nursing to the mastectomized woman. The following felt question is about a descriptive study of qualitative boarding that it used as referencial theoretician the Symbolic Interacionismo and the Theory Based on Data Ground Theory as referencial metodológic, on the basis of: how the nurse perceives its process of communication with the mastectomized woman? The collection of data occurred in the months of June and July of 2006 in an institution of reference in the treatment of the cancer. We use as strategy for collection of data the interview with nine nurses who gave assistance to the mastectomized woman. We got then, the data that the analysis had after allowed the creation of the central theory: The meaning of the communication in the assistance of nursing to the mastectomized woman, which consists of three distinct phenomena that if interrelate. They are they: One to look at on the communication, that is characterized as a process of the theory where the phenomena that had led the nurses to reflect on its way of communication with the mastectomized woman had been elucidated emerging meanings and values to its respect; identifying the rocks of the way, that point the main difficulties found in the implantation of a communication accomplishes between patient nurse/, including the limitations personal; e rethink the communication nurse/woman mastectomized, who emphasizes the meaning attributed for the nurse to its necessity to remain itself sensetized to the communication process accomplishes with the mastectomized woman, in intention to give optimum possible care. This significant interaction emerges when the nurse uses itself of its communication ability, perceiving the patient and interacting with it, provoking changes and seeing the woman as a social being, that is, attributing one meant to it. In our opinion, for a satisfactory communication the installment of the human being care, the professional who works in the assistance the women mastectomized necessary to become involved itself and to believe that its presence is so important how much the accomplishment of procedures technician, therefore, in general way, the objective knowledge technician function so well ahead of situations of estresse how much the subjective knowledge that if disclose in the therapeutical communication.